The Relationship of Parental Attention to Learning Motivation of Elementary School Students - Yeni Yeni; Susan Neni Triani; Mertika Mertika (Pedagogik Journal of Islamic Elementary School, 2023)
This study aims to: 1) To describe the relationship between parental attention to student learning motivation; 2) To describe the learning motivation of fourth grade students of SDN 90 Singkawang; 3) To determine the relationship of parental attention to the learning motivation of grade IV students of SDN 90 Singkawang. The independent variable in this study is parental attention denoted by (X), while the dependent variable in this study is student learning motivation denoted by (Y), this type of research is descriptive with simple total sampling design. The sample in this study were IVB class students. The sample in this study were IV B class students of SD Negeri 90 Singkawang, totaling 25 people. Data obtained through a questionnaire of parental attention and a questionnaire of student learning motivation. The data analysis technique used is Pearson product moment correlation. The results showed that: there is a significant relationship between parental attention and student learning motivation.  This shows that the value of r count 0.525> r table 0.36. From this explanation it can be concluded that this hypothesis test states that there is a relationship between parental attention and student learning motivation.